PENGARUH PENERAPAN SISTEM E-FILING, E-BILLING, DAN SANKSI PAJAK TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Ihsan Frendy Anshari; Banu Witono (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the effect of the Implementation of the E-Filing System, E-Biling, and Tax Sanctions on the Compliance Level of Individual Taxpayers with Case Studies at the Primary Tax Service Office in the Surakarta Karasidenan. This research uses quantitative methods using a survey approach. The population in this study is individual taxpayers registered at the Surakarta Karasidenan Tax Office. Data were collected through questionnaires distributed to 60 respondents selected using convenience sampling technique. The variables measured in this study include the application of the e-filing system, e-billing and tax sanctions and the level of compliance of individual taxpayers. The data were analyzed using multiple linear regression analysis. The results showed that the Application of E-Filling has a significant effect on taxpayer compliance while, E-Billing and Tax Sanctions have no significant effect on individual taxpayer compliance. These findings indicate that convenience and efficiency in the tax reporting process through E-Filing have an important role in increasing individual taxpayer compliance. Meanwhile, the application of E-Billing and the provision of tax sanctions has not been able to have a significant effect on the level of compliance, which may be due to a lack of understanding, socialization, or effectiveness of these two aspects in practice.